Self-Acceptance Process as an Idea in the Creation of Graphic Art - Hasanah, Fi'luna Maungidhotul (Journal of Contemporary Indonesian Art, 2024)
The process of creating art is often closely intertwined with the direct experiences of an artist. Various emotions experienced during the journey towards self-acceptance have the potential to serve as sources of inspiration, with empirical experiences encompassing a range of feelings such as sadness, disappointment, or even feelings of inadequacy, to acceptance and gratitude in everyday life. Efforts to depict the journey of self-acceptance involve presenting excerpts of self-acceptance stories, the acceptance process, and the array of emotions felt by the artist into graphic art. The symbolic manifestation of the artwork is supported by realistic figures, presenting the journey of self-acceptance with relevant idioms to support ideas using high printing techniques.